An evaluation of the robustness of global amphibian range maps. (16th September 2013) - Ficetola, Gentile Francesco; Rondinini, Carlo; Bonardi, Anna; Katariya, Vineet; Padoa‐Schioppa, Emilio; Angulo, Ariadne; Pearson, Richard
Abstract Aim Maps of species ranges are among the most frequently used distribution data in biodiversity studies. As with any biological data, range maps have some level of measurement error, but this error is rarely quantified. We assessed the error associated with amphibian range maps by comparing them with point locality data. Location Global. Methods The maps published by the Global Amphibian Assessment were assessed against two data sets of species point localities: the Global Biodiversity Information Facility (GBIF), and a refined data set including recently published, high‐quality presence data from both GBIF and other sources. Range fit was measured as the proportion of presence records falling within the range polygon(s) for each species. Results Using the high‐quality point data provided better fit measures than using the raw GBIF data. Range fit was highly variable among continents, being highest for North American and European species (a fit of 84–94%), and lowest for Asian and South American species (a fit of 57–64%). At the global scale, 95% of amphibian point records were inside the ranges published in maps, or within 31 km of the range edge. However, differences among continents were striking, and more points were found far from range edges for South American and Asian species. Main conclusions The Global Amphibian Assessment range maps represent the known distribution of most amphibians well; this study provides measures of accuracy that can be useful for future research using amphibian maps as baseline data. Nevertheless, there is a need for greater investment in the continuous updating and improvement of maps, particularly in the megadiverse areas of tropical Asia and South America.